2020
DOI: 10.12659/msm.921162
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Radix Astragali on Cholangiocarcinoma In Vitro and Its Mechanism via Network Pharmacology

Abstract: Background:This study used network pharmacology method and cell model to assess the effects of Radix Astragali (RA) on cholangiocarcinoma (CCA) and to predict core targets and molecular mechanisms. Material/Methods:We performed an in vitro study to assess the effect of RA on CCA using CCK8 assay, the Live-Cell Analysis System, and trypan blue staining. The components and targets of RA were analyzed using the Traditional Chinese Medicine Systems Pharmacology database, and genes associated with CCA were retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Because of the complex pharmacological nature of multicompound-multitarget-multipathway agents, there is often a fundamental limitation in investigating their comprehensive mechanisms of action based only on conventional biological experimental methodologies [61][62][63][64][65][66][67][68]. To overcome such challenges, network pharmacology, an integrative research field that systematically combines computational systems biology, network science, medicine, pharmacology, mathematics, and physics, has emerged as one of the most effective approaches for the mechanistic exploration of polypharmacological drugs, such as herbal medicines [61][62][63][64][65][66][67][68]. e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the complex pharmacological nature of multicompound-multitarget-multipathway agents, there is often a fundamental limitation in investigating their comprehensive mechanisms of action based only on conventional biological experimental methodologies [61][62][63][64][65][66][67][68]. To overcome such challenges, network pharmacology, an integrative research field that systematically combines computational systems biology, network science, medicine, pharmacology, mathematics, and physics, has emerged as one of the most effective approaches for the mechanistic exploration of polypharmacological drugs, such as herbal medicines [61][62][63][64][65][66][67][68]. e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such challenges, network pharmacology, an integrative research field that systematically combines computational systems biology, network science, medicine, pharmacology, mathematics, and physics, has emerged as one of the most effective approaches for the mechanistic exploration of polypharmacological drugs, such as herbal medicines [61][62][63][64][65][66][67][68]. e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68]. Previous network pharmacology studies successfully investigated the polypharmacological properties of herbal drugs by identifying their active compounds and key therapeutic targets and further elucidating the distinct system-level pharmacological effects and mechanisms (e.g., therapeutic modulation of biological processes such as proliferation, apoptosis, cell cycle regulation, angiogenesis, oxidation and reduction, insulin metabolism, and inflammation) for the treatment of various diseases, including cancer, diabetes, arthritis, and ischemic stroke, which are exerted by the synergistic interplay between multiple compounds and targets contained in herbal drugs [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al showed the other Astragalus-based herbal prescription (SH003) could alleviate docetaxel-induced neuropathic pain [ 138 ]. Studies also showed that the components included in Astragali radix have an anti-cancer effect [ 139 , 140 ] and help to prevent nephrotoxicity and hepatotoxicity induced by the anti-cancer drugs [ 73 ]. These further suggest the usefulness of this substance in anti-cancer therapy.…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…This research approach produces distinct types of herbal-drug-associated networks by merging relevant comprehensive pharmacological, medicinal, and biomolecular data 10-17 . This is followed by an investigation of the topological and functional characteristics of the networks, which contributes to the systematic understanding of the treatment mechanisms of herbal drugs 10-17 . Using network pharmacology, we determined the anti-OC potential of FDY003 from a comprehensive systems view.…”
Section: Introductionmentioning
confidence: 99%